Stand Alone Papers 2022 2022
DOI: 10.3390/proceedings2022080003
|View full text |Cite
|
Sign up to set email alerts
|

A Trend Analysis of Research on the Flipped Classroom in L2 Learning before and after COVID-19

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…This study found that students who use the OFC in class are better able to understand and read texts than those who do not (Aidoo et al, 2022;Barrios et al, 2022;Köksal & Han, 2022).…”
mentioning
confidence: 82%
“…This study found that students who use the OFC in class are better able to understand and read texts than those who do not (Aidoo et al, 2022;Barrios et al, 2022;Köksal & Han, 2022).…”
mentioning
confidence: 82%